Bleeding risk assessment and management in atrial fibrillation patients - Lip, Gregory Y. H.; Andreotti, Felicita; Fauchier, Laurent; Huber, Kurt; Hylek, Elaine; Knight, Eve; Lane, Deirdre; Levi, Marcel; Marin, Francisco; Palareti, Gualtiero; Kirchhof, Paulus; Collet, J.-P.; Rubboli, A.; Poli, D.; Camm, A. J. (Thrombosis and Haemostasis, 2011)
In this executive summary of a Consensus Document from the European Heart Rhythm Association, endorsed by the European Society of Cardiology Working Group on Thrombosis, we comprehensively review the published evidence and propose a consensus on bleeding risk assessments in atrial fibrillation (AF) patients. The main aim of the document was to summarise ‘best practice’ in dealing with bleeding risk in AF patients when approaching antithrombotic therapy, by addressing the epidemiology and size of the problem, and review established bleeding risk factors. We also summarise definitions of bleeding in the published literature. Patient values and preferences balancing the risk of bleeding against thromboembolism as well as the prognostic implications of bleeding are reviewed. We also provide an overview of published bleeding risk stratification and bleeding risk schema. Brief discussion of special situations (e.g. periablation, peri-devices such as implantable cardioverter defibrillators [ICD] or pacemakers, presentation with acute coronary syndromes and/or requiring percutanous coronary interventions/stents and bridging therapy) is made, as well as a discussion of the prevention of bleeds and managing bleeding complications. Finally, this document puts forwards consensus statements that may help to define evidence gaps and assist in everyday clinical practice.
Keywords: Bleeding; oral anticoagulation; atrial fibrillation; risk assessment